2004
DOI: 10.1091/mbc.e03-08-0558
|View full text |Cite
|
Sign up to set email alerts
|

Human Topoisomerase IIα: Targeting to Subchromosomal Sites of Activity during Interphase and Mitosis

Abstract: Mammalian topoisomerase IIalpha (topo IIalpha) plays a vital role in the removal of topological complexities left on DNA during S phase. Here, we developed a new assay to selectively identify sites of catalytic activity of topo IIalpha with subcellular resolution. We show that topo IIalpha activity concentrates at replicating heterochromatin in late S in a replication-dependent manner and at centric heterochromatin during G2 and M phases. Inhibitor studies indicate that this cell cycle-dependent concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 42 publications
7
46
0
Order By: Relevance
“…In agreement with previous studies reporting that Topo-II remains active in mitosis (Agostinho et al, 2004;Rattner et al, 1996), we found that soluble, endogenous Topo-II was at least as active as a recombinant Topo-II preparation, while retaining normal susceptibility to (Fig. 3C).…”
Section: Relationship Between Cohesin Removal and Centromere Decatenasupporting
confidence: 93%
“…In agreement with previous studies reporting that Topo-II remains active in mitosis (Agostinho et al, 2004;Rattner et al, 1996), we found that soluble, endogenous Topo-II was at least as active as a recombinant Topo-II preparation, while retaining normal susceptibility to (Fig. 3C).…”
Section: Relationship Between Cohesin Removal and Centromere Decatenasupporting
confidence: 93%
“…Indeed, enzymatically active topoisomerase IIα is concentrated in heterochromatin in mid-late S-phase in HeLa cells and is delocalized by the HDACI TSA. 38 We have studied the nuclear distribution of topoisomerase IIβ and show here that TSA leads to its redistribution in the nucleus and a change in the pattern of topoisomerase IIβ-DNA complexes induced by etoposide in favour of a more euchromatic pattern. We suggest that altering the distribution of topoisomerase IIβ in the nucleus and thus topoisomerase IIβ-DNA adducts across the genome converts topoisomerase IIβ into a more clinically useful target for topoisomerase poisons including etoposide.…”
Section: Histone Deacetylase Inhibition Redistributes Topoisomerase Imentioning
confidence: 89%
“…In a variation of this approach adherent cells are extracted in a similar fashion on glass coverslips under slightly less harsh conditions (DRT extraction) without agarose embedding. 38 We used this latter technique to examine the effect of TSA treatment on both the quantity and subnuclear distribution of topoisomerase IIβ-DNA complexes. While very low levels of nuclear topoisomerase IIβ fluorescence were observed in DRT-extracted control cells, in cells treated with etoposide topoisomerase IIβ immunofluorescence was easily detectable (Figs.…”
Section: A Fraction Of Topoisomerase Iiβ Is Concentrated In Heterochrmentioning
confidence: 99%
“…It is possible that the topo II␣ we consistently found associated with endogenous APC and with the M2-APC fragment ( Figures 1B and 6B) corresponds to a specific pool of topo II␣ involved in regulation of the G2/M transition. Other pools of topo II␣ might be positioned near replicating heterochromatin during S phase (Agostinho et al, 2004), tightly associated with DNA to aid chromosome assembly at the G2/M transition (Earnshaw and Heck, 1985;Gasser et al, 1986;Swedlow and Hirano, 2003), responsible for transcription regulation at G1/S (Huang et al, 2007), or involved in chromosome segregation at the exit of mitosis (Hirano and Mitchison, 1993;Downes et al, 1994;Grue et al, 1998). One explanation for the rather modest amount of topo II␣ that coprecipitated with endogenous APC is that the interaction between APC and topo II␣ is transient, only occurring at a specific point of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%